2021
DOI: 10.3389/fenrg.2021.686561
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Fiscal Decentralization on Garbage Classifications

Abstract: China has been promoting garbage classification in its rural areas, yet it lacks financial appropriation and fiscal decentralization to support waste processing projects. Though the existing literature has suggested fiscal decentralization strategies between different local government levels, few of the studies ascertain garbage classification efficiency from a quantitative perspective. To bridge the gap, this study examines the optimal fiscal decentralization strategies for garbage classification. It uses an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Internal factors mainly include environmental concern (Stern et al, 1995), pollution perception (Jia et al, 2021), perceived environmental regulation (Xu et al, 2023) and so on. External factors mainly include economic subsidy (Zen and Siwar, 2015;Xu et al, 2018), environmental monitoring (Li X. et al, 2019), fiscal decentralization (Ma et al, 2021), digital governance (Chen et al, 2023a) and so on. All of these will have an impact on farmers' waste separation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Internal factors mainly include environmental concern (Stern et al, 1995), pollution perception (Jia et al, 2021), perceived environmental regulation (Xu et al, 2023) and so on. External factors mainly include economic subsidy (Zen and Siwar, 2015;Xu et al, 2018), environmental monitoring (Li X. et al, 2019), fiscal decentralization (Ma et al, 2021), digital governance (Chen et al, 2023a) and so on. All of these will have an impact on farmers' waste separation behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the published literature, the factors can be divided into internal and external factors. The internal factors are mainly based on psychological cognitive perspectives such as environmental concern ( 8 ), waste governance cognition ( 9 ), environmental governance perceptions ( 10 ), and altruistic preferences ( 11 ). The external factors are mainly environmental, such as economic incentives ( 12 , 13 ), transportation conditions ( 14 ), fiscal decentralization ( 8 ), environmental advocacy, and monitoring ( 15 ), and political participation ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The internal factors are mainly based on psychological cognitive perspectives such as environmental concern ( 8 ), waste governance cognition ( 9 ), environmental governance perceptions ( 10 ), and altruistic preferences ( 11 ). The external factors are mainly environmental, such as economic incentives ( 12 , 13 ), transportation conditions ( 14 ), fiscal decentralization ( 8 ), environmental advocacy, and monitoring ( 15 ), and political participation ( 16 ). In addition, some scholars have also found that the consistency between rural residents' willingness to separate domestic waste and their separation behavior is low based on the theory of planned behavior ( 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…From a research perspective, there are more examinations from a cost-benefit perspective (Yaman, 2012;Kinnaman, 2014;Di Foggia and Beccarello, 2020), and few scholars have conducted research from a spatial-geographical perspective. From the perspective of factors influencing individuals, scholars have mainly examined the impact of internal and external factors on individual waste treatment behavior (willingness to treat waste and level of waste treatment) such as environmental concern (Stern et al, 1995), waste governance cognition (Zeng et al, 2016), environmental governance perceptions (Wang and Hao, 2020), economic incentives (Xu et al, 2018), transportation conditions (Liu and Huang, 2014), fiscal decentralization (Ma et al, 2021), environmental advocacy and monitoring (Li X. R. et al, 2019). In addition, some scholars introduce initiatives and experiences of waste treatment in other countries (Lv and Du, 2016;Yang et al, 2019), with a view to providing methodological references for urban waste treatment in China.…”
Section: Introductionmentioning
confidence: 99%